Trend in obtaining career information in the digital era within the context of post-covid-19 career anxiety - Meylia Sari; Abu Yazid Abu Bakar; Yuda Syahputra (Jurnal Konseling dan Pendidikan, 2023)
The aim of this study was to analyze trend in obtaining career information in the digital era within the context of post-COVID-19 career anxiety. This was a comparative descriptive study and the data were obtained through random sampling. The sample consisted of 267 students randomly selected from various universities in East Aceh. Furthermore, career anxiety scale was used as the main measurement tool, which has high reliability with Cronbach's alpha of 0.85 and item reliability in Rasch 0.98. Descriptive analysis and ANOVA test were used to analyze the data. The results showed significant differences in level of post-COVID-19 career anxiety based on gender and addiction level. However, in the context of career information, there were no statistically significant differences. Another interesting result was that career information from friends remained trend in the digital era, and this trend persisted till present. Therefore, the results of this study can be used as a basis for the development of programs to overcome career anxiety.